Seasonal Variations in Crustal Seismicity in San‐in District, Southwest Japan. Issue 6 (21st March 2019) - Ueda, T.; Kato, A.
Abstract: A growing body of evidence suggests that seismicity is seasonally modulated in a variety of tectonic environments. Identifying cyclic variations in seismicity improves our understanding of the physics of earthquake triggering. We explored seasonal modulation of crustal seismicity in San‐in district, southwest Japan, using a new method that adopts uncertainties derived from a probability‐based declustering procedure. We determined that semiannual variation in background seismicity rate, which increases in spring and autumn, is statistically significant from 1980 to 2017. The frequency distribution of large historic and modern earthquakes shows a similar pattern to recent background seismicity, suggesting that seismicity in San‐in district has shown seasonal variations for over 150 years. These observations can be explained by increasing pore pressure within fault zones, caused by precipitation in autumn and decreasing surface mass due to snow melting in spring. Plain Language Summary: Seismic activity is seasonally modulated by surface processes. To explore earthquake seasonality, it is necessary to choose only independent earthquakes from entire seismicity catalog; this selection process is called earthquake declustering. Here, we introduce a new statistical declustering method to evaluate the significance of seasonal modulation of shallow seismicity, which includes an estimate of the uncertainty associated with earthquake declustering. We apply this technique to shallow crustal seismicity in San‐in district, southwest Japan. The rate of independent earthquakes from 1980 to 2017 shows significant semiannual variation, with increases in spring and autumn. The distribution of large historic and modern earthquakes shows similar variations, suggesting that seismicity in San‐in district has been related to the seasons for at least 150 years. This seasonality can be attributed to heavy precipitation in autumn and snow melting in spring. Seasonal modulation of small earthquakes should be monitored to investigate temporal changes in the probabilities of large earthquakes in San‐in district. Key Points: A new method evaluates the significance of earthquake seasonality adopting uncertainty derived from a stochastic declustering scheme The background seismicity rate of San‐in district in Japan shows significant semiannual variation that increases in spring and autumn Seasonal variations in seismicity can be explained by heavy precipitation in autumn and snow melting in spring